2020
DOI: 10.3390/electronics9091410
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Voltage Inverter-Based Operational Transconductance Amplifiers with Voltage Gain Enhancement by Improved Composite Transistors

Abstract: This paper proposes topological enhancements to increase voltage gain of ultra-low-voltage (ULV) inverter-based OTAs. The two proposed improvements rely on adoption of composite transistors and forward-body-biasing. The impact of the proposed techniques on performance figures is demonstrated through simulations of two OTAs. The first OTA achieves a 39 dB voltage gain, with a power consumption of 600 pW and an active area of 447 μm2. The latter allies the forward-body-bias approach with the benefit of the indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Inverter-based OTA topologies [11,12] and their respective ULV variations [13,14] have been proposed, as well as push-pull-based, bulk-driven OTAs [15][16][17][18]. An improved single-ended OTA has been proposed in [19], exploiting the properties of improved composite transistors [20] into a variation of the bulk Nauta inverter-based OTA [21]. This approach improves the voltage gain for a single-stage amplifier but shows a limited input voltage swing.…”
Section: Introductionmentioning
confidence: 99%
“…Inverter-based OTA topologies [11,12] and their respective ULV variations [13,14] have been proposed, as well as push-pull-based, bulk-driven OTAs [15][16][17][18]. An improved single-ended OTA has been proposed in [19], exploiting the properties of improved composite transistors [20] into a variation of the bulk Nauta inverter-based OTA [21]. This approach improves the voltage gain for a single-stage amplifier but shows a limited input voltage swing.…”
Section: Introductionmentioning
confidence: 99%
“…The OTA reported in [20] operates with a supply voltage of 1 V and exhibits state of the art small-signal and large-signal figures of merit. Unfortunately, most of these conventional amplifier topologies are not suited for applications requiring supply voltages lower than 0.5 V, and inverter-based [21][22][23][24][25][26] and pseudo-differential [27,28] architectures are preferred. However, an aggressive supply voltage scaling severely limits the swing of the control voltage, thus strongly limiting the effectiveness of body bias approaches to set the bias or the common mode current.…”
Section: Introductionmentioning
confidence: 99%
“…Additional approaches have also been proposed to replace OTAs, though not for general purpose usage, including dynamic amplifiers [11], ring amplifiers [12], and zero-crossing based circuits [13]. In addition, one interesting trend is the use of inverter-based topologies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. (A good review of the principal techniques for low-voltage OTAs can be found in the last reference.)…”
Section: Introductionmentioning
confidence: 99%